Association between Medication Adherence and Health-related Quality of Life in Patients Diagnosed with Chronic Obstructive Pulmonary Disease: A Prospective Study - Mrs. Bandla Aswani, (Asian Journal of Pharmaceutics (AJP), 2025)
Introduction: Chronic obstructive pulmonary disease (COPD) is one of the third leading causes of death globally. The degree of drug adherence and health-related quality of life (HRQOL) in COPD patients is low. COPD significantly reduces patients’ HRQOL, with symptoms and exacerbations affecting physical, emotional, and social well-being. With frequent hospitalizations and healthcare consumption driving expenditures and resource utilization, COPD is one of the world’s leading causes of morbidity and mortality, and also significantly strains healthcare systems. Purpose of the Study: The purpose of this study is to investigate the association between medication adherence and HRQOL in COPD patients. Materials and Methods: This study was hospital-based cross-sectional observational study conducted in the Department of Medicine Sri Venkateswara Institute of Medical Sciences, South India, a tertiary care hospital, Tirupati, Andhra Pradesh. This study was approved by the Institutional Research and the Ethics Committee of the hospital. This observational study was performed on 70 patients diagnosed with COPD. Each patient was interviewed to answer questionnaires regarding demographic and clinical information. To assess HRQOL in COPD patients, the St George’s respiratory questionnaire-COPD-specific version was used. The medication adherence reporting scale was used to measure medication adherence. Statistical analysis was conducted using the Statistical Package for the Social Sciences, version 20. Results: Out of 70 patients who are undergoing treatment for COPD in the medicine department, 60% (42) of the patients have medium medication adherence, 30% (21) have low medication adherence, and 10% (7) of patients have high medication adherence. HRQOL shows a positive effect on medication adherence. Discussion: The positive correlation observed between adherence and HRQOL may be explained by improved disease stability, as patients who follow their treatment plans are more likely to experience fewer respiratory symptoms, enhanced physical functioning, and a greater sense of control over their condition. Conclusion: This prospective study highlights a significant positive association between medication adherence and HRQOL in patients with COPD. Patients who consistently adhered to their prescribed medication regimen reported better outcome in both physical and mental domains of HRQOL compared to those with poor adherence.